AN ANALYTICAL STUDY ON THE IMPACT OF INDIAN COLLEGIUM SYSTEM IN JUDICIAL APPOINTMENTS WITH RESPECT TO OTHER DEMOCRACIES - S, Gangadhara; Aithal, K R (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The etymology of the word ‘court’ denotes an enclosed place. Be it an enclosed yard as derived from the French term Cour or a garden of horticulture or orchard as descended from the Latin word ‘hortus’ or an ancient Greek word ‘Khortos’, which gives the significance of the roles and responsibilities assigned to or vested with the court systems in the world. The judicial assembly since its inception from the 12th Century designates the sovereign and his/her entourage to adjudicate disputes in an enclosed yard or a space. Judiciaries being the collective system of courts interpret and apply laws of the land. A Bench is formed by a Judge or body of judges whereas a Bar is structured by attorneys and barristers. The ‘venue’ is a place where the court sits. If the administration of justice could be handled well with utmost efficiency and effectiveness by the first known democratic administration in the world, the Water Court at Valencia, an ancient coastal city in the Western Spain. It would be an eyeopener for the judiciary to see how efficiently the irrigators of the Valencia plain could manage their water resources. The researchers try to highlight the very purpose for which the courts, even in the ancient times, were established and the way they functioned by the sovereign and his / her team of experts and competent administrators. The reflections clearly indicate the need for preserving the sanctity of free and fair principles without compromising impartial and unbiased decrees as pronounced or expected to be promulgated by the judges while upholding the democratic integrity and republican values.